Preparation method and application of high-modulus heterocyclic aramid fiber
By controlling the reaction conditions and adding modified nanoalumina powder, the problem of insufficient modulus of existing heterocyclic aramid fibers was solved, and high-modulus fibers were prepared to meet the mechanical requirements of high-end applications such as aerospace.
Patent Information
- Application Number
- CN202411988251.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing heterocyclic aramid fibers have insufficient modulus and are difficult to meet the mechanical requirements of high-end applications such as aerospace.
By controlling the reaction temperature and the addition amount of terephthalyl chloride, using p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole as raw materials, high-modulus heterocyclic aramid fibers were prepared, and modified nanoalumina powder was added to the fiber stock solution to improve the breaking strength and modulus of the fibers.
The prepared high-modulus heterocyclic aramid fibers exhibit excellent break strength, elongation of break and initial modulus, and are suitable for high-end fields such as aerospace, defense and military industry.
Smart Images

Figure BDA0005223079930000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fiber-reinforced composite materials, and more specifically, to a preparation method and application of high modulus heterocyclic aramid fiber. Background Art
[0002] Aramid fibers are mainly divided into three types: meta-aramid, para-aramid and heterocyclic aramid. Heterocyclic aramid, also known as aramid III and heterocyclic aromatic polyamide fiber, refers to high-performance fibers made by introducing heterocyclic structural units on the basis of traditional aramid structure. Compared with ordinary aramid, heterocyclic aramid has the advantages of good mechanical properties, good chemical stability, good thermal stability, good flame retardancy, good photoelectric properties, etc. It is mainly used in aerospace, national defense and military industry, civil safety protection equipment, construction engineering, automobile manufacturing and communication systems.
[0003] Heteroaramid fibers are often used to make composite materials. Increasing the modulus of the fiber can enhance the overall performance of the composite material, such as increasing the tensile strength and modulus of the composite material, making it more adaptable to various complex application environments. Increasing the modulus of heteroaramid fibers can enhance their ability to resist deformation, allowing the material to maintain a more stable shape when subjected to stress, thereby improving the overall structural strength and durability. High-modulus heteroaramid fibers can meet the needs of more high-end applications. For example, in the aerospace field, high-modulus fibers can withstand greater mechanical loads, help reduce the weight of the aircraft, and improve flight efficiency. Therefore, the preparation of high-modulus heteroaramid fibers has become a hot spot in the development of the heteroaramid fiber industry. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a high modulus heterocyclic aramid fiber is provided, comprising the following steps:
[0006] Step 1, adding solvent and co-solvent into the reaction kettle;
[0007] Step 2: Lower the temperature of the reaction kettle to -5 to 5°C, add p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole, and stir to dissolve;
[0008] Step 3, adding terephthaloyl chloride into the reaction kettle twice, the first addition amount is 80-90% of the total molar amount, reacting for 6-18 hours and then raising the reaction temperature to room temperature; adding the remaining terephthaloyl chloride to react until a viscous heterocyclic aramid stock solution is obtained;
[0009] Step 4: Degassing and filtering the heterocyclic aramid stock solution before spinning, and the spinneret is stretched and heat treated to obtain high modulus heterocyclic aramid fibers.
[0010] Preferably, in step 1, the solvent is N,N-dimethylacetamide or N-methylpyrrolidone; the co-solvent is lithium chloride, sodium acetate or lithium acetate; wherein the co-solvent accounts for 1.5-3.0% of the mass of the solvent.
[0011] Preferably, the usage ratio of the solvent, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and terephthaloyl chloride is 1000-3000 g: 0.1-0.5 mol: 0.2-0.5 mol: 0.3-1.0 mol.
[0012] Preferably, in the step 1, the reactor further comprises modified nano-alumina powder and a surfactant, sodium dodecyl sulfate, and the amount ratio of the modified nano-alumina powder, sodium dodecyl sulfate and solvent is 1-10g:0.5-2g:1000-3000g.
[0013] Preferably, the preparation method of the modified nano alumina powder comprises:
[0014] S1. Dispersing nano-alumina powder with a particle size of 20 to 50 nm in deionized water to obtain a suspension, adding polyethylene glycol-600 to the suspension to coat the nano-alumina powder, and after adding polyethylene glycol-600, ultrasonically dispersing the suspension at an ultrasonic frequency of 30 to 50 kHz for 10 to 20 minutes, and standing for 2 to 12 hours to obtain a dispersion;
[0015] S2, adding graphene powder to the dispersion, stirring and heating to 30-60° C., keeping warm for 20-30 min, heating to 80-90° C., keeping warm for 5-10 min, then cooling to room temperature, standing for 2-4 h, to obtain a mixed dispersion;
[0016] S3, evaporating and concentrating the mixed dispersion, filtering, washing and drying the precipitate to obtain a solid powder;
[0017] S4. The solid powder is subjected to vacuum heat treatment, the vacuum degree is less than 0.02 Pa, the heat treatment temperature is 200-400° C., the heat treatment time is 5-20 min, and the modified nano-alumina powder is obtained after cooling to room temperature.
[0018] Preferably, in S1, the usage ratio of nano-alumina powder, polyethylene glycol-600 and deionized water is 2-10 g: 1-5 mL: 250-300 mL.
[0019] Preferably, in S2, the D90 particle size of the graphene powder is 0.3 μm, and the mass ratio of the graphene powder to the nano-alumina powder is 1-3:2-10.
[0020] Preferably, in the step 4, the stretching amount of the spinneret in the coagulation bath is 120-150%, the coagulation bath temperature is 20-60° C., the spinneret aperture is 0.05-0.15 mm, and the number of holes is 100-500 holes.
[0021] Preferably, in step 4, the heat treatment temperature is 200-400°C.
[0022] An application of high modulus heterocyclic aramid fiber, which is used in the processing and manufacturing of materials and composite materials in the fields of aerospace, national defense and military industry, civilian safety protection equipment, construction engineering, automobile manufacturing and communication systems.
[0023] The present invention includes at least the following beneficial effects: the present invention uses p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole as raw materials, and controls the reaction temperature and the amount of terephthaloyl chloride added to prepare heterocyclic aramid fibers that exhibit excellent breaking strength, breaking elongation and initial modulus, and can be widely used in the processing and manufacturing of materials and composite materials in the fields of aerospace, national defense and military industry, civil safety protection equipment, construction engineering, automobile manufacturing, and communication systems.
[0024] The invention adds polyethylene glycol-600 and graphene-coated modified nano-alumina powder to the heterocyclic aramid stock solution, and through the dispersing effect of sodium dodecyl sulfate, the modified nano-alumina powder is evenly dispersed in the heterocyclic aramid stock solution, thereby improving the uniformity of the modified nano-alumina powder in the reaction system, thereby improving the uniformity of the modified nano-alumina powder in the heterocyclic aramid fiber and reducing the difficulty of spinning. In addition, the addition of the modified nano-alumina powder significantly improves the breaking strength, breaking elongation and initial modulus of the heterocyclic aramid fiber.
[0025] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0026] The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0027] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0028] Example 1
[0029] This embodiment provides a method for preparing a high modulus heterocyclic aramid fiber, comprising the following steps:
[0030] Step 1: Add 3000 g of N,N-dimethylacetamide as a solvent and 60 g of lithium acetate as a co-solvent into a reaction kettle;
[0031] Step 2: Lower the temperature of the reaction kettle to 0°C, add 21.6 g of p-phenylenediamine and 67.2 g of 2-(4-aminophenyl)-5-aminobenzimidazole, and stir to dissolve;
[0032] Step 3, 101.5g of terephthaloyl chloride was added to the reactor twice, with the first addition amount being 81.2g. After reacting for 12 hours, the reaction temperature was raised to 25°C; the remaining 20.3g of terephthaloyl chloride was added to react until a viscous heterocyclic aramid stock solution was obtained;
[0033] Step 4: degassing the heterocyclic aramid stock solution at normal pressure for 6 hours, filtering and spinning, and the spinneret is stretched and heat-treated to obtain high modulus heterocyclic aramid fiber; wherein the stretching amount of the spinneret in the coagulation bath is 120%, the coagulation bath temperature is 40°C, the spinneret aperture is 0.10 mm, the number of holes is 300, and the heat treatment temperature is 250°C.
[0034] Example 2
[0035] This embodiment provides a method for preparing a high modulus heterocyclic aramid fiber, comprising the following steps:
[0036] Step 1: Add 2500 g of N,N-dimethylacetamide as a solvent and 37.5 g of lithium acetate as a co-solvent into a reaction kettle;
[0037] Step 2: Lower the temperature of the reaction kettle to 5°C, add 32.4g of p-phenylenediamine and 44.8g of 2-(4-aminophenyl)-5-aminobenzimidazole, and stir to dissolve;
[0038] Step 3: Add 60.9 g of terephthaloyl chloride into the reactor in two portions, with the first portion adding 55.2 g. After reacting for 12 hours, raise the reaction temperature to 25° C.; add the remaining 11.7 g of terephthaloyl chloride and react until a viscous heterocyclic aramid stock solution is obtained;
[0039] Step 4: degassing the heterocyclic aramid stock solution at normal pressure for 6 hours, filtering and spinning, and the spinneret is stretched and heat-treated to obtain high modulus heterocyclic aramid fiber; wherein the stretching amount of the spinneret in the coagulation bath is 120%, the coagulation bath temperature is 40°C, the spinneret aperture is 0.10 mm, the number of holes is 300, and the heat treatment temperature is 250°C.
[0040] Example 3
[0041] This embodiment provides a method for preparing a high modulus heterocyclic aramid fiber, comprising the following steps:
[0042] Step 1: Add 2000 g of N,N-dimethylacetamide as a solvent and 50 g of lithium acetate as a co-solvent into a reaction kettle;
[0043] Step 2: Lower the temperature of the reaction kettle to -5°C, add 10.8 g of p-phenylenediamine and 44.8 g of 2-(4-aminophenyl)-5-aminobenzimidazole, and stir to dissolve;
[0044] Step 3: Add 60.9 g of terephthaloyl chloride into the reactor in two portions, with the first portion adding 55.2 g. After reacting for 12 hours, raise the reaction temperature to 25° C.; add the remaining 11.7 g of terephthaloyl chloride and react until a viscous heterocyclic aramid stock solution is obtained;
[0045] Step 4: degassing the heterocyclic aramid stock solution at normal pressure for 6 hours, filtering and spinning, and the spinneret is stretched and heat-treated to obtain high modulus heterocyclic aramid fiber; wherein the stretching amount of the spinneret in the coagulation bath is 120%, the coagulation bath temperature is 50°C, the spinneret cap aperture is 0.10 mm, the number of holes is 100, and the heat treatment temperature is 300°C.
[0046] Example 4
[0047] This embodiment provides a method for preparing high modulus heterocyclic aramid fiber. The difference from Embodiment 1 is that in step 1, 2 g of modified nano-alumina powder and 1 g of sodium dodecyl sulfate are added. The method for preparing the modified nano-alumina powder includes:
[0048] S1. Disperse 10 g of nano-alumina powder with a particle size of 20 to 50 nm in 250 mL of deionized water to obtain a suspension, add 2 mL of polyethylene glycol-600 to the suspension to coat the nano-alumina powder, and after adding polyethylene glycol-600, ultrasonically disperse at an ultrasonic frequency of 30 kHz for 20 min, let stand for 12 h, and obtain a dispersion;
[0049] S2, adding 2 g of graphene powder with a D90 particle size of 0.3 μm to the dispersion, stirring and heating to 60° C., keeping the temperature for 30 min, then heating to 90° C., keeping the temperature for 5 min, then cooling to room temperature, and standing for 3 h to obtain a mixed dispersion;
[0050] S3, evaporating and concentrating the mixed dispersion, filtering, washing and drying the precipitate to obtain a solid powder;
[0051] S4. The solid powder is subjected to vacuum heat treatment, the vacuum degree is less than 0.02 Pa, the heat treatment temperature is 200° C., the heat treatment time is 20 min, and the modified nano alumina powder is obtained after cooling to room temperature.
[0052] The methods and process parameters of the remaining steps of this embodiment are the same as those of Embodiment 1.
[0053] Example 5
[0054] This embodiment provides a method for preparing high modulus heterocyclic aramid fiber. The difference from Embodiment 1 is that in step 1, 5 g of modified nano-alumina powder and 1.5 g of sodium dodecyl sulfate are added. The method for preparing the modified nano-alumina powder includes:
[0055] S1. Disperse 10 g of nano-alumina powder with a particle size of 20 to 50 nm in 250 mL of deionized water to obtain a suspension, add 2 mL of polyethylene glycol-600 to the suspension to coat the nano-alumina powder, and after adding polyethylene glycol-600, ultrasonically disperse the suspension at an ultrasonic frequency of 40 kHz for 15 min, let stand for 12 h, and obtain a dispersion;
[0056] S2, add 2.5g D90 graphene powder with a particle size of 0.3μm to the dispersion, stir and heat to 50°C, keep warm for 20-30min, then heat to 90°C, keep warm for 5min, then cool to room temperature, stand for 4h, and obtain a mixed dispersion;
[0057] S3, evaporating and concentrating the mixed dispersion, filtering, washing and drying the precipitate to obtain a solid powder;
[0058] S4. The solid powder is subjected to vacuum heat treatment, the vacuum degree is less than 0.02 Pa, the heat treatment temperature is 300° C., the heat treatment time is 10 min, and the modified nano-alumina powder is obtained after cooling to room temperature.
[0059] The methods and process parameters of the remaining steps of this embodiment are the same as those of Embodiment 1.
[0060] Example 6
[0061] This embodiment provides a method for preparing high modulus heterocyclic aramid fiber. The difference from Embodiment 1 is that in step 1, 10 g of modified nano-alumina powder and 2 g of sodium dodecyl sulfate are added. The method for preparing the modified nano-alumina powder includes:
[0062] S1. Disperse 10 g of nano-alumina powder with a particle size of 20 to 50 nm in 250 mL of deionized water to obtain a suspension, add 3 mL of polyethylene glycol-600 to the suspension to coat the nano-alumina powder, and after adding polyethylene glycol-600, ultrasonically disperse the suspension at an ultrasonic frequency of 50 kHz for 20 min, let stand for 12 h, and obtain a dispersion;
[0063] S2, add 3g of graphene powder to the dispersion, stir and heat to 60°C, keep warm for 30min, then heat to 90°C, keep warm for 10min, then cool to room temperature, stand for 4h, and obtain a mixed dispersion;
[0064] S3, evaporating and concentrating the mixed dispersion, filtering, washing and drying the precipitate to obtain a solid powder;
[0065] S4. The solid powder is subjected to vacuum heat treatment, the vacuum degree is less than 0.02 Pa, the heat treatment temperature is 400° C., the heat treatment time is 20 min, and after cooling to room temperature, a modified nano-alumina powder is obtained.
[0066] The methods and process parameters of the remaining steps of this embodiment are the same as those of Embodiment 1.
[0067] Comparative Example 1
[0068] This comparative example provides a method for preparing high modulus heterocyclic aramid fiber. Different from Example 1, 5 g of nano-alumina powder with a particle size of 20 to 50 nm and 1.5 g of sodium dodecyl sulfate are added in step 1. The preparation methods and process parameters of the remaining steps of this comparative example are the same as those in Example 1.
[0069] Comparative Example 2
[0070] This comparative example provides a method for preparing high modulus heterocyclic aramid fiber. Different from Example 1, 10 g of nano-alumina powder with a particle size of 20 to 50 nm and 2 g of sodium dodecyl sulfate are added in step 1 of this comparative example. The preparation methods and process parameters of the remaining steps of this comparative example are the same as those of Example 4.
[0071] The breaking strength (measurement method refers to GB / T19975-2005), breaking elongation (measurement method refers to GJB348-87) and initial modulus (measurement method refers to GB / T 42823-2023) of the high modulus heterocyclic aramid fibers prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were measured respectively, and the following table was obtained:
[0072]
[0073] It can be seen from the above table that the high modulus heterocyclic aramid fibers prepared in Examples 1 to 6 all have relatively high breaking strength, breaking elongation and initial modulus. Among them, modified nano-alumina powder is added to the heterocyclic aramid stock solution of Examples 4 to 6, and the breaking strength, breaking elongation and initial modulus of the prepared heterocyclic aramid fibers are further improved.
[0074] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0075] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the examples shown and described herein.
Claims
1. A method for preparing high modulus heterocyclic aramid fiber, characterized in that: The following steps are involved: Step 1, adding solvent and co-solvent into the reaction kettle; Step 2: Lower the temperature of the reaction kettle to -5 to 5°C, add p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole, and stir to dissolve; Step 3, adding terephthaloyl chloride into the reaction kettle twice, the first addition amount is 80-90% of the total molar amount, reacting for 6-18 hours and then raising the reaction temperature to room temperature; adding the remaining terephthaloyl chloride to react until a viscous heterocyclic aramid stock solution is obtained; Step 4: Degassing and filtering the heterocyclic aramid stock solution before spinning, and the spinneret is stretched and heat treated to obtain high modulus heterocyclic aramid fibers.
2. The method for preparing high modulus heterocyclic aramid fiber according to claim 1, characterized in that: In the step 1, the solvent is N,N-dimethylacetamide or N-methylpyrrolidone; the co-solvent is lithium chloride, sodium acetate or lithium acetate; wherein the co-solvent accounts for 1.5-3.0% of the solvent mass.
3. The method for preparing high modulus heterocyclic aramid fiber according to claim 1, characterized in that: The usage ratio of the solvent, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and terephthaloyl chloride is 1000-3000 g: 0.1-0.5 mol: 0.2-0.5 mol: 0.3-1.0 mol.
4. The method for preparing high modulus heterocyclic aramid fiber according to claim 1, characterized in that: In the step 1, the reactor further comprises modified nano-alumina powder and a surfactant, sodium dodecyl sulfate, and the amount ratio of the modified nano-alumina powder, sodium dodecyl sulfate and solvent is 1-10g: 0.5-2g: 1000-3000g.
5. The method for preparing high modulus heterocyclic aramid fiber according to claim 4, characterized in that: The preparation method of the modified nano alumina powder comprises: S1. Dispersing nano-alumina powder with a particle size of 20 to 50 nm in deionized water to obtain a suspension, adding polyethylene glycol-600 to the suspension to coat the nano-alumina powder, and after adding polyethylene glycol-600, ultrasonically dispersing the suspension at an ultrasonic frequency of 30 to 50 kHz for 10 to 20 minutes, and standing for 2 to 12 hours to obtain a dispersion; S2, adding graphene powder to the dispersion, stirring and heating to 30-60° C., keeping warm for 20-30 min, heating to 80-90° C., keeping warm for 5-10 min, then cooling to room temperature, standing for 2-4 h, to obtain a mixed dispersion; S3, evaporating and concentrating the mixed dispersion, filtering, washing and drying the precipitate to obtain a solid powder; S4. The solid powder is subjected to vacuum heat treatment, the vacuum degree is less than 0.02 Pa, the heat treatment temperature is 200-400° C., the heat treatment time is 5-20 min, and the modified nano-alumina powder is obtained after cooling to room temperature.
6. The method for preparing high modulus heterocyclic aramid fiber according to claim 5, characterized in that: In the S1, the usage ratio of nano-alumina powder, polyethylene glycol-600 and deionized water is 2-10 g: 1-5 mL: 250-300 mL.
7. The method for preparing high modulus heterocyclic aramid fiber according to claim 5, characterized in that: In S2, the D90 particle size of the graphene powder is 0.3 μm, and the mass ratio of the graphene powder to the nano-alumina powder is 1-3:2-10.
8. The method for preparing high modulus heterocyclic aramid fiber according to claim 1, characterized in that: In the step 4, the stretching amount of the spinneret in the coagulation bath is 120-150%, the coagulation bath temperature is 20-60° C., the spinneret hole diameter is 0.05-0.15 mm, and the number of holes is 100-500 holes.
9. The method for preparing high modulus heterocyclic aramid fiber according to claim 1, characterized in that: In the step 4, the heat treatment temperature is 200-400°C.
10. An application of high modulus heterocyclic aramid fiber, characterized in that: The high modulus heterocyclic aramid fiber is prepared by the preparation method of the high modulus heterocyclic aramid fiber according to any one of claims 1 to 9, and the high modulus heterocyclic aramid fiber is used in the processing and manufacturing of materials and composite materials in the fields of aerospace, national defense and military industry, civil safety protection equipment, construction engineering, automobile manufacturing, and communication systems.
Citation Information
Patent Citations
High-performance heterocyclic aramid fiber as well as preparation and application thereof
CN101921395A
Preparation method of alpha-nanometer alumina oxide modified polyester fibers
CN107723833A
Preparation method of graphene enhanced polyester fibers
CN107988650A
Heterocyclic aramid fiber and preparation method thereof
CN114990723A
High-wear-resistance and high-toughness nylon monofilament and preparation method thereof
CN118957795A